Prediagnostic serum levels of inflammatory biomarkers are correlated with future development of lung and esophageal cancer. Issue 9 (3rd September 2014) - Keeley, Brieze R.; Islami, Farhad; Pourshams, Akram; Poustchi, Hossein; Pak, Jamie S.; Brennan, Paul; Khademi, Hooman; Genden, Eric M.; Abnet, Christian C.; Dawsey, Sanford M.; Boffetta, Paolo; Malekzadeh, Reza; et al.
<x xml:space="preserve">Abstract</x> This study tests the hypothesis that prediagnostic serum levels of 20 cancer‐associated inflammatory biomarkers correlate directly with future development of head and neck, esophageal, and lung cancers in a high‐risk prospective cohort. This is a nested case–control pilot study of subjects enrolled in the Golestan Cohort Study, an ongoing epidemiologic project assessing cancer trends in Golestan, Iran. We measured a panel of 20 21cytokines, chemokines, and inflammatory molecules using Luminex technology in serum samples collected 2 or more years before cancer diagnosis in 78 aerodigestive cancer cases and 81 controls. Data was analyzed using Wilcoxon rank sum test, odds ratios, receiver operating characteristic areas of discrimination, and multivariate analysis. Biomarkers were profoundly and globally elevated in future esophageal and lung cancer patients compared to controls. Odds ratios were significant for association between several biomarkers and future development of esophageal cancer, including interleukin‐1Rα (IL‐1Ra; 35.9), interferon α2 (IFN‐a2; 34.0), fibroblast growth factor‐2 (FGF‐2; 17.4), and granulocyte/macrophage colony‐stimulating factor (GM‐CSF; 17.4). The same pattern was observed among future lung cancer cases for G‐CSF (27.7), GM‐CSF (13.3), and tumor necrosis factor‐α (TNF‐a; 8.6). By contrast, the majority of biomarkers studied showed no significant correlation with future head and neck cancer development. This study provides the first direct evidence that multiple inflammatory biomarkers are coordinately elevated in future lung and esophageal cancer patients 2 or more years before cancer diagnosis.